Keratoconus: advances in anterior lamellar keratoplasty techniques. (2nd January 2020) - Scorcia, Vincenzo; Giannaccare, Giuseppe; Logozzo, Laura; Soda, Mauro
ABSTRACT: Introduction : Deep anterior lamellar keratoplasty (DALK) is nowadays considered the gold standard for the surgical treatment of keratoconus thanks to the lower rate of complications compared to conventional penetrating keratoplasty (PK). However, the learning curve and the suboptimal quality of donor-recipient interface still remain debated issues. Areas covered : To date, big-bubble DALK (BB-DALK) is the most widely performed technique. However, the introduction of femtosecond laser has given new impulse to the standardization of DALK, but also new drawbacks to deal with. Furthermore, the recent redefinition of corneal anatomy understanding along with the introduction of novel techniques have provided further advantages in terms of success rate and postoperative visual outcomes. Expert commentary : Although DALK is still dependent on single surgeon experience and skills, techniques and tools employed are quickly evolving thus improving surgical outcomes. However, to date, there is no universal consensus about alternative options in case of BB-DALK failure as well as management of intra-operative complications.